Gene deletion reveals roles for annexin A1 in the regulation of lipolysis and IL-6 release in epididymal adipose tissue. - Warne, J; John, C; Christian, H; Morris, J; Flower, R; Sugden, D; Solito, E; Gillies, G; Buckingham, J (2006)
In this study, epididymal adipose tissue from male annexin 1 (ANXA1)-null and wild-type control mice were used to explore the potential role of ANXA1 in adipocyte biology. ANXA1 was detected by Western blot analysis in wild-type tissue and localized predominantly to the stromal-vascular compartment. Epididymal fat pad mass was reduced by ANXA1 gene deletion, but adipocyte size was unchanged, suggesting that ANXA1 is required for the maintenance of adipocyte and/or preadipocyte cell number. Epididymal tissue from wild-type mice responded in vitro to noradrenaline and isoprenaline with increased glycerol release, reduced IL-6 release, and increased cAMP accumulation. Qualitatively similar but significantly attenuated responses to the catecholamines were observed in tissue from ANXA1-null mice, an effect that was not associated with changes in beta-adrenoceptor mRNA expression. Lipopolysaccharide (LPS) also stimulated lipolysis in vitro, but its effects were muted by ANXA1 gene deletion. By contrast, LPS failed to influence IL-6 release from wild-type tissue but stimulated the release of the cytokine from tissue from ANXA1-null mice. ANXA1 gene deletion did not affect glucocorticoid receptor expression or the ability of dexamethasone to suppress catecholamine-induced lipolysis. It did, however, augment IL-6 expression and modify the inhibitory effects of glucocorticoids on IL-6 release. Collectively, these studies suggest that ANXA1 supports aspects of adipose tissue mass and alters the sensitivity of epididymal adipose tissue to catecholamines, glucocorticoids, and LPS, thereby modulating lipolysis and IL-6 release.